2018
DOI: 10.18311/mvpjms/2018/v5/i1/20044
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Supreme LMA Vs I-gel : Two Supraglottic Airway Devices in Short Surgical Procedures"

Abstract: Background and Aims: The objective of this prospective, randomized trial was to compare I-Gel with Supreme LMA in anaesthetized spontaneously breathing patients for short surgical procedures. Material and Methods: Sixty patients of ASAI -ASAII of either gender between 18-60 years undergoing short surgical procedures were randomly assigned to I-gel (Group I) or LMA-Supreme (Group S). After induction with propofol the supraglottic airway device was inserted. We compared the ease and time required for insertion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Shin et al, 13 study also showed that there was no difference in the hemodynamic characteristics between the two SADs. The hemodynamic parameters between the two groups were in accordance with studies conducted by Govardhane et al, 14 Helmy et al, 15 and Teoh et al 3 The success rate in first attempt was comparable between two groups. The success rate of insertion in first attempt in group S (LMA-S) was 85% as compared to 80% in group I (I-gel).…”
Section: Discussionsupporting
confidence: 89%
“…Shin et al, 13 study also showed that there was no difference in the hemodynamic characteristics between the two SADs. The hemodynamic parameters between the two groups were in accordance with studies conducted by Govardhane et al, 14 Helmy et al, 15 and Teoh et al 3 The success rate in first attempt was comparable between two groups. The success rate of insertion in first attempt in group S (LMA-S) was 85% as compared to 80% in group I (I-gel).…”
Section: Discussionsupporting
confidence: 89%